ANALISIS PENGARUH PENDAPATAN, HARGA, DAN TINGKAT KONSUMSI ISLAMI TERHADAP PEMBELIAN DI MINIMARKET AL-KHAIBAR MASJID ROIS DAHLAN - Mujahid, Muhammad Azzam; Muljaningsih, Sri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
In Indonesia, traditional markets are expected to shift to modern markets such as minimarkets, as evidenced by the number of minimarkets in Indonesia. Product availability, income, and comparing product prices in stores are things that can influence the increase in consumers in making purchases at mini markets. The development that occurs in minimarkets can also be known through the number of consumers who make purchases. The purpose of this research is to find out how the variables of income, price, and Islamic consumption level affect purchases at the Rois Dahlan Mosque minimarket. The data obtained is primary data sourced from the results of questionnaires that have been distributed to respondents, namely 30 consumers who shop at the Al-Khaibar minimarket of the Rois Dahlan Mosque. This study uses logistic regression analysis using the SPSS 27 program. The results showed that income, price and Islamic consumption levels simultaneously affect the chances of increasing purchases. From the partial test results, it is found that the price variable and the level of Islamic consumption have a significant effect on the opportunity to increase purchases. While the income variable does not have a significant effect on the opportunity to increase purchases.